Japanese Adult-Onset Type 1 Diabetic Sisters with Different Disease States: A Case Report - Kusumoto, Koshi; Koriyama, Nobuyuki; Kojima, Nami; Ikeda, Maki; Nishio, Yoshihiko (Archives of Clinical and Medical Case Reports, 2020)
We encountered type 1 diabetic sisters with different islet-associated antibodies and pancreatic β-cell injury rates. The younger sister had different disease susceptibility human leukocyte antigen (HLA) haplotypes (DRB1*0901-DQB1*0303/DRB1*0802-DQB1*0302) on both chromosomes, while the older sister showed a disease susceptibility HLA haplotype (DRB1*0901-DQB1*0303/-) on one chromosome. Furthermore, the younger sister was positive for anti-glutamic acid decarboxylase antibody (GADA), anti-insulinoma-associated protein-2 antibody (IA-2A), and zinc transporter 8 antibody (ZnT8A), and showed depleted endogenous insulin secretory ability at the time of diagnosis. On the other hand, the older sister was positive only for GADA and ZnT8A, and the ability to secrete endogenous insulin was relatively retained at onset. From our cases and existing reports, we verified that: 1) having a HLA haplotype for disease susceptibility on both chromosomes; 2) having HLA-DQ8 and HLA-A24, -DQA1*03 and -DR9; 3) having more islet autoantibodies including IA-2A and ZnT8A may be involved in accelerating the progression of type 1 diabetes by enhancing the damage to pancreatic β-cells.